Identification and sequence analysis of a novel human leukocyte antigen allele B*51:141. Issue 1 (6th December 2012) - Caggiari, L.; De Zorzi, M.; Izzo, F.; Tornesello, M. L.; Buonaguro, F. M.; De Re, V.
<x xml:space="preserve">Abstract</x> The newly detected HLA‐B*51:141 is distinguished from HLA‐B*51:08 by a single‐nucleotide exchange at codon 30 where D is replaced by Y.